A Paradigm Development of Community Learning Management in the Small Sized School in Buri Ram Province Thailand - Kiyasit, Kovit; Kultanan, Phatchanee; Vajarintarangoon, Kovit; Wannupatam, Benchaporn; Sosutha, Chaloemchai; Chusuwan, Suwimon (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
The objectives from this research were to 1) develop and find out the efficiency of a community-based learning paradigm to promote creative thinking for teachers in the small-sized school, 2) study the effectiveness of a community based learning paradigm management to promote creative thinking for teachers in the small-sized school, and 3) study the satisfaction of developing a community-based learning paradigm as a creative thinking paradigm for teachers in the small-sized school. This research was Research and Development (R&D) combined with the design of a single sample system. The research instrument used in the research was a learning management paradigm community based learning with three learning units and creative thinking evaluation form. The data was analyzed by average, standard deviation, and t-test dependent. The findings of this research are: 1) The efficiency of a community-based learning paradigm to promote creative thinking for teachers in the small-sized school in Buri Ram Province was 81.20/82.50, 2) The effectiveness of a community-based learning paradigm to promote creative thinking for teachers in the small-sized school in Buri Ram Province was that post-training session based on the paradigm of community-based learning management was higher than pre-training session significantly at 0.05, and 3) satisfaction in developing a community-based learning paradigm to promote creative thinking for teachers in the small-sized school in Buri Ram Province was very high. This study implies that the learning paradigm of the community needs to be applied so that creative thinking skills could be improved.